Investigating the Impact of Lactic Acid Accumulation, Body Composition, Swimming Velocity, and Cardiovascular Responses on Performance in 100-Meter Freestyle Swimming (International Journal of Scientific Research in Science and Technology, 2024)
This study evaluates the impact of lactic acid accumulation, body composition, swimming velocity, and cardiovascular responses on the performance of 100-meter freestyle swimmers. The 100-meter freestyle is a highly demanding event that requires a precise balance of physical and physiological factors to achieve optimal performance. Lactic acid buildup during high-intensity efforts can lead to muscular fatigue and affect performance, making its management crucial for competitive swimmers. Body composition, including muscle mass and body fat percentage, plays a significant role in determining swimming efficiency and speed, influencing how effectively swimmers can maintain their velocity over the distance. Swimming velocity itself is a direct measure of performance, reflecting the swimmer’s overall technique and conditioning. Cardiovascular responses, including heart rate and VO2 max, provide insights into the swimmer’s aerobic capacity and how well their body manages oxygen during intense exertion. This study employs a multifaceted approach, combining physiological testing, body composition analysis, velocity measurements, and cardiovascular assessments. Techniques such as lactate threshold testing, bioelectrical impedance analysis (BIA), high-speed video analysis, and heart rate monitoring are used to gather comprehensive data. By examining the interactions among these variables, the research aims to identify key predictors of performance and to provide evidence-based recommendations for training and performance enhancement. Understanding these relationships can lead to more effective training strategies, optimized race preparation, and improved overall performance in 100-meter freestyle swimming, offering valuable insights for swimmers, coaches, and sports scientists alike.